STUDY ON INTERNAL CONTROL OF SUPPLIERS AND CUSTOMERS IN A CONSTRUCTION COMPANY - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
Control covers debts and liabilities, outstanding liabilities and purchases and expenses in the profit and loss and long-term liabilities, provisions and funding costs. The validation tests applied to cover all, claims liabilities in the financial statements but with less emphasis on testing for registration. It can be done but circularize commercial debt is often not necessary because suppliers provide documentary evidence statements from third parties. Direct circularization of claims is a basic procedure, but it does not provide evidence for all relevant assertions. Other important procedures are: tests of independence; testing for the possibility of recovery.